2014
DOI: 10.3126/ije.v3i2.10521
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variation in maize inbred lines

Abstract: In order to identify morphological variation in maize inbred lines, one hundred five inbred lines were planted under randomized complete block design with two replications at research field of National Maize Research Program, Rampur, Chitwan, Nepal during summer season (March to June), 2010. Descriptive statistics and cluster analysis were done. The results revealed a wide range of morphological variation among the tested inbred lines. The inbred lines grouped in cluster 4 namely PUTU-13, L-9, RL-105, RL-197, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 4 publications
4
13
0
1
Order By: Relevance
“…Observed variability for grain yield, 100-seed weight, and panicle weight were similar to earlier reports in sorghum [8, 12, 14] and maize [25, 26]. The results of this study showed that the majority of the Benin sorghum landraces had very tall height, large leaf area, and large number of internodes.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Observed variability for grain yield, 100-seed weight, and panicle weight were similar to earlier reports in sorghum [8, 12, 14] and maize [25, 26]. The results of this study showed that the majority of the Benin sorghum landraces had very tall height, large leaf area, and large number of internodes.…”
Section: Discussionsupporting
confidence: 89%
“…Application of PCA tool and multivariate statistical analysis provide useful means to estimate morphological diversity within and between germplasm collections [8, 20, 25, 26]. In this study, five axes contributed 73.8% of total diversity among the accessions.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Prasai et al (2015) also reported genetic variability on early maize. Similarly, Shrestha (2014) observed morphological variation in maize inbred lines in Chitwan, Nepal.…”
Section: Analysis Of Variancementioning
confidence: 76%
“…Its genetic diversity has been characterized by morphological traits, pedigree analysis, heterosis data, biochemical and DNA molecular markers (Smith and Smith, 1989;Jambrovic et al, 2008;Srdic et al, 2008;Ranatunga et al, 2009;Lauer et al, 2012;Shrestha, 2013).…”
Section: Introductionmentioning
confidence: 99%